Urgensi Regulasi Ketahanan dan Keamanan Siber dalam Undang-Undang ITE - Muhamamad Arief (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2022)
The case of the BPJS data leak containing the personal data of 279 million Indonesians and the circulation of the BMKG SMS blast containing false information has become a public spotlight because it indicates the weakness of the personal data protection system and national cyber security. Until now, there is no specific regulation that comprehensively regulates cyber security and resilience. The Ministry of Communication and Information of the Republic of Indonesia (Kominfo) supports the ratification of the Cyber Security and Resilience Bill, especially for securing critical infrastructure and completing the Electronic Information and Transaction Law